1992
DOI: 10.1051/jp1:1992271
|View full text |Cite
|
Sign up to set email alerts
|

Terrace sizes in molecular beam epitaxy

Abstract: The order of magnitude of the typical distance ℓ between steps in MBE-grown crystal surfaces in calculated from simple scaling assumptions in the absence of evaporation. This distance is measurable by diffraction methods and yields access to the surface diffusion constant D. At the lowest non trivial temperatures the characteristic distance is of order (D/F)1/6 where F is the beam flux. At slightly higher temperature, ℓ is given by an algebraic formula which depends on the lifetime τ2 of a bound pair of adatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
145
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(152 citation statements)
references
References 0 publications
7
145
0
Order By: Relevance
“…We have checked that, as in the case of a continuous flux [3,10], the saturation island density is reached for a surface coverage of about 15%. Then, the total number of cycles needed to reach saturation is n c ∼ f /(6F i d).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…We have checked that, as in the case of a continuous flux [3,10], the saturation island density is reached for a surface coverage of about 15%. Then, the total number of cycles needed to reach saturation is n c ∼ f /(6F i d).…”
Section: Introductionmentioning
confidence: 95%
“…Summary, Perspectives : As anticipated, we have shown that it is not possible to interpret growth experiments under a chopped flux in the framework of usual growth models [3][4][5] …”
mentioning
confidence: 98%
See 3 more Smart Citations